Digital Visual Selective Attention System (VSAS) Platform Based on Sociotechnical Design to Encourage Communication and Democratic Participation in Indonesia - Amin, Zaid; Zinaida, Rahma Santhi; Regina V. H., Genoveva; Aprinda, Ria (PT Mattawang Mediatama Solution, 2023)
Demonstrating attentive behavior when users decide to share information on social media is vital. Such attentiveness helps users more effectively identify misinformation, allowing them to avoid being misled by hidden deceptive content. The rapid increase of information in online media today means that the dissemination of misinformation can have serious negative consequences, such as threatening political stability and democracy, which can lead to societal divisions. While many studies have investigated the traceability and prediction of misinformation spread, additional research is necessary to understand and prevent the disruptions in human attention that contribute to this issue. This leads to questions about how technological interventions can enhance user awareness during the decision-making process of sharing information, especially to promote honest and constructive communication in a democratic context. The objective of this research is to examine and intervene in the factors of user attention when sharing information online, particularly regarding communication and democratic participation in Indonesia. This study employs a mixed-methods design, combining both quantitative and qualitative approaches. It is structured into two phases: Study 1 involves an investigation into the importance of attention factors in social media sharing through a self-report survey with adult participants from Palembang. Additionally, in Study 2, we designed and tested a Visual Selective Attention System (VSAS) using a Sociotechnical Design approach to influence decision-making by implementing an attention-focused design. We hope that the future development of interactions within a VSAS-based social media application will yield sustainable insights that encourage a non-coercive approach to managing the sharing of misinformation, thereby supporting transparent and fair communication and democratic participation (LUBER and JURDIL) in Indonesia.